2015
DOI: 10.1016/j.ijrobp.2014.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Relapse From a Phase 3 Study of Response-Based Therapy for Intermediate-Risk Hodgkin Lymphoma (AHOD0031): A Report From the Children's Oncology Group

Abstract: Purpose The study was designed to determine whether response-based therapy improves outcomes in intermediate-risk Hodgkin lymphoma. We examined patterns of first relapse in the study. Methods From 9/02 – 7/10, 1712 patients <22 yrs of age with stage I–IIA with bulk, I–IIAE, I–IIB, and IIIA–IVA with/without bulk were enrolled. Patients were categorized as rapid (RER) or slow early responders (SER) after 2 cycles of doxorubicin, bleomycin, vincristine, etoposide, prednisone, and cyclophosphamide (ABVE-PC). SER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 26 publications
(25 reference statements)
2
16
0
Order By: Relevance
“…In another study, Wray et al [16] evaluated 17 pediatric patients treated with PT and reported three recurrences, including two among patients with advanced stage IV disease. All three of those recurrences had a component of infield recurrence after 21-25.5 Gy, similar to the pattern of recurrence seen after photon radiation to 21 Gy in pediatric HL [17] and what was seen in the present study. ABVD: doxorubicin (Adriamycin), bleomycin, vinblastine, and dacarbazine; ABVE-PC: doxorubicin (Adriamycin), bleomycin, vincristine, etoposide, prednisone, and cyclophosphamide.…”
Section: Discussionsupporting
confidence: 88%
“…In another study, Wray et al [16] evaluated 17 pediatric patients treated with PT and reported three recurrences, including two among patients with advanced stage IV disease. All three of those recurrences had a component of infield recurrence after 21-25.5 Gy, similar to the pattern of recurrence seen after photon radiation to 21 Gy in pediatric HL [17] and what was seen in the present study. ABVD: doxorubicin (Adriamycin), bleomycin, vinblastine, and dacarbazine; ABVE-PC: doxorubicin (Adriamycin), bleomycin, vincristine, etoposide, prednisone, and cyclophosphamide.…”
Section: Discussionsupporting
confidence: 88%
“…Considering that all the recurrences in our cohort had an in‐field component, our observations are consistent with AHOD0031 and suggest that higher radiation doses similar to the doses used in ECOG 2496 should be considered for slow responders in upcoming trials. Such guidelines are in fact included in AHOD 1331 for patients with Deauville 3 or higher disease on completing chemotherapy …”
Section: Discussionmentioning
confidence: 73%
“…In pediatrics, the Children’s Oncology Group has conducted studies to utilize response-adapted IFRT in intermediate-risk cHL. 13 An analysis of treatment failures confirmed that initially involved sites are most likely to relapse after chemotherapy (but not exclusively). The authors speculated that consolidative ISRT may be a strategy to address such areas at risk while reducing the organ and tissue radiation risks of IFRT.…”
Section: Involved Site Radiation Therapymentioning
confidence: 93%